Pengaruh Kompetensi Sumber Daya Manusia (SDM) Terhadap Efektivitas Kinerja Pegawai Di Dinas Pendidikan, Kepemudaan, Dan Olahraga Kabupaten Bantul - Yanti Kristiani Zalukhu (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the influence of human resource (HR) competence on the effectiveness of employee performance at the Department of Education, Youth, and Sports of Bantul Regency. This research uses a quantitative approach with primary data as the main data source. The population in this study includes all employees at DIKPORA Bantul Regency. The data analysis technique used is simple linear regression, with the equation Y = 1.099 + 0.564X. Based on the t-test, the result shows that = 11.758 = 1.672 and the significance value is 0.000 < 0.05. Therefore, the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted. This means that HR competence has a significant influence on the effectiveness of employee performance at the Department of Education, Youth, and Sports of Bantul Regency.